2020
DOI: 10.1155/2020/6710503
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about COVID-19 and Practices among Hemodialysis Technicians in the COVID-19 Pandemic Era

Abstract: Introduction. Hemodialysis technicians play a crucial role in infection control practices in hemodialysis units. Thus, it is important to assess the knowledge and attitude towards COVID-19 among hemodialysis technicians in this pandemic situation. Materials and Methods. An online survey composed of 22 closed-ended questions using Google Forms was conducted in the month of April (13th to 19th) 2020. The survey consisted of questions regarding the knowledge of COVID-19 and current hemodialysis practice among hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Similar study about Dengue was reported by Meshram et al [33]. Pasari et al assessed knowledge about covid-19 and practices among hemodialysis technicians [34]. Swapnil P. et al reported on knowledge, attitude and practices of allied health care professional students towards universal precaution [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 68%
“…Similar study about Dengue was reported by Meshram et al [33]. Pasari et al assessed knowledge about covid-19 and practices among hemodialysis technicians [34]. Swapnil P. et al reported on knowledge, attitude and practices of allied health care professional students towards universal precaution [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 68%
“…al. reported on Interleukin-6 as predictor of 'non-alcoholic fatty liver disease' among 'insulin resistance syndrome' patients [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Right training of health professionals to deal with any eventualities. Proper dissemination of information right from the top will ensure people taking right decisions and not fall into the pray of Infodemic , Pasari, A.S. et al 2020, Pate, m.y., et al 2020and Quazi, A.A., and m. Patil. 2020.…”
Section: Divergence Of All the Resources To Fight Covid-19mentioning
confidence: 99%